Increased carotenoid content of Xanthophyllomyces dendrorhous cultivated in plant oil supplemented media - Csernetics, Árpád (Acta Biologica Szegediensis, 2007)
Carotenoid pigments (particularly astaxanthin) of the red yeast Xanthophyllomyces dendrorhous (Phaffia rhodozyma) have economical importance as food and feed colouring additives. Application of nutrients stimulating astaxanthin synthesis would improve the pigment production of the fungus. Vegetable oils contain various unsaturated fatty acids and isoprenoids, among them different precursors of the carotenoid biosynthesis. Th e effect of seven different, commercially available vegetable oils (sesame seed oil, corn seed oil, wheat germ oil, palm oil, pumpkin seed oil, coconut oil and olive oil) on the carotenoid production of two strains representing the teleomorph X. dendrorhous and the anamorph P. rhodozyma was examined. The two strains responded to the presence of the oil additives distinctly. Sesame seed and coconut oil stimulated the pigment production in the X. dendrorhous isolate only, whereas palm oil increased the production of both tested strains.